2014
DOI: 10.1039/c3mb70462a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of protein kinase identification via high dimensional protein–protein interactions and substrate structure data

Abstract: As a crucial post-translational modification, protein phosphorylation regulates almost all basic cellular processes. Recently, thousands of phosphorylation sites have been discovered by large-scale phospho-proteomics studies, but only about 20% of them have information regarding catalytic kinases, which brings a great challenge for correct identification of the protein kinases responsible for experimentally verified phosphorylation sites. In most existing identification tools, only a local sequence was selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…We also carefully checked the literature and UniProt database34, and all known site-specific HAT-substrate relations (ssHSRs) in the prediction results were pinpointed (Supplementary Table S4). Previously, it was demonstrated that various functional features of proteins, such as gene ontology (GO) annotations and protein-protein interactions (PPIs), were beneficial for the prediction of kinase-specific phosphorylation sites4041. In this work, the GO information was not used, because the functional diversity of HAT-specific acetylated substrates was high and no particularly significant GO terms were detected from the statistical enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We also carefully checked the literature and UniProt database34, and all known site-specific HAT-substrate relations (ssHSRs) in the prediction results were pinpointed (Supplementary Table S4). Previously, it was demonstrated that various functional features of proteins, such as gene ontology (GO) annotations and protein-protein interactions (PPIs), were beneficial for the prediction of kinase-specific phosphorylation sites4041. In this work, the GO information was not used, because the functional diversity of HAT-specific acetylated substrates was high and no particularly significant GO terms were detected from the statistical enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ten-fold cross-validation as described in existing studies (Gao et al, 2010; Xu et al, 2014a; Xue et al, 2006) was applied to assess the predictive performance of the proposed method. For a given PTM, 9/10 randomly chosen samples were used as the training data while the remaining 1/10 were used as the test data.…”
Section: Methodsmentioning
confidence: 99%
“…During the past few decades, many efforts including experimental strategies and computational approaches have been undertaken to identify potential PTM sites (Fan et al, 2014; Gao et al, 2016; Xu et al, 2014a), and most of these methods used local sequence information for prediction due to the fact that PTMs generally occur at specific yet conserved motif in the target protein (Blom, Gammeltoft & Brunak, 1999; Eisenhaber & Eisenhaber, 2010; Miller & Blom, 2009). For example, to predict phosphorylation sites, a number of local sequence based tools have been developed, such as GPS 2.0 (Xue et al, 2008), Musite (Gao et al, 2010), PhosphoSVM (Dou, Yao & Zhang, 2014), NetPhos (Blom et al, 2004) and KinasePhos 2.0 (Wong et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We ranked all 315 features with a widely used filtering feature selection algorithm mRMR [19] (1) while the redundancy between the feature s i and all other selected features is donated as RED and calculated by…”
Section: B Classifier Creationmentioning
confidence: 99%
“…However, large amount of features with redundant and noisy data may leave heavy burden on the classifier, which usually leads to decreased performance [19] [20]. To remedy this shortcoming, recently several phosphorylation site prediction approaches incorporating different feature selection methods were proposed.…”
Section: Introductionmentioning
confidence: 99%